Biological and molecular features of Nosema rachiplusiae sp. n., a microsporidium isolated from the neotropical moth Rachiplusia nu (Guenée) (Lepidoptera: Noctuidae) - Arneodo Larochette, Joel Demian; Sciocco, Alicia Ines (Springer, 2018)
Light, electron microscopy and DNA analyses were performed to characterize a microsporidium infecting Rachiplusia nu larvae from a laboratory rearing in Argentina. Diplokaryotic spores were oval and measured 3.61 ± 0.29 × 1.61 ± 0.14 μM (fresh). The spore wall was composed of an electron-dense exospore and an electron-lucent endospore, ca. 30 nm and 100–120 nm thick, respectively. The polar filament was arranged in a single rank of 10–12 coils (typically 11). Microsporidian cells were found in the cytoplasm, next to the endoplasmic reticulum (especially the prespore stages) and generally surrounded by electron-lucent spaces. The infection was polyorganotropic; the fat body appeared as the most heavily invaded tissue, followed by tracheal matrix and epidermis. A molecular phylogeny based on the small (SSU) and large subunit (LSU) ribosomal RNA genes clearly placed the new isolate within the “Nosema bombycis clade”. Considering both SSU and LSU concatenated partial sequences, the microsporidium from R. nu showed 99.5% nucleotide similarity with N. bombycis and 99.8% with its closest relative, a microsporidium isolated from Philosamia cynthia. According to its genetic and biological features, the R. nu isolate is proposed as the new species Nosema rachiplusiae sp. n., expanding the limited knowledge on microsporidia associated to endemic South-American moths.